2022
DOI: 10.1111/jocd.15087
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic update on the 3‐dimensionality of the subdermal septum and its relevance for the pathophysiology of cellulite

Abstract: Background Cellulite is an aesthetic condition affecting the appearance of skin in specific body regions. When reviewing past literature, a 2‐D image of a subdermal septum was created most likely due to the applied cross‐sectional investigative methodology. Despite practitioners being aware of the 3‐D nature of the subdermal architecture, this is not reflected in the present scientific literature. The aim of this anatomic review is to summarize the past literature and to provide an update on the 3‐dimensionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…1,6 In men, the septa stretch from the dermal undersurface at a 45°angle and form a crisscross pattern, resulting in smaller fat lobules and a denser subdermal arrangement. 2,3,[7][8][9] In women, the septa are oriented perpendicularly to the skin and are less numerous, resulting in larger fat lobules and less structural stability, thereby allowing subdermal adipose tissue to become displaced. 9,10 Estrogen may also play a role in cellulite development because of involvement in adipocyte hypertrophy, lipogenesis, and collagen formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,6 In men, the septa stretch from the dermal undersurface at a 45°angle and form a crisscross pattern, resulting in smaller fat lobules and a denser subdermal arrangement. 2,3,[7][8][9] In women, the septa are oriented perpendicularly to the skin and are less numerous, resulting in larger fat lobules and less structural stability, thereby allowing subdermal adipose tissue to become displaced. 9,10 Estrogen may also play a role in cellulite development because of involvement in adipocyte hypertrophy, lipogenesis, and collagen formation.…”
mentioning
confidence: 99%
“…2,3,[7][8][9] In women, the septa are oriented perpendicularly to the skin and are less numerous, resulting in larger fat lobules and less structural stability, thereby allowing subdermal adipose tissue to become displaced. 9,10 Estrogen may also play a role in cellulite development because of involvement in adipocyte hypertrophy, lipogenesis, and collagen formation. 11 Studies and surveys have demonstrated that cellulite can negatively affect self-esteem, body image, and quality of life.…”
mentioning
confidence: 99%